Spirocyclic Delta Opioid Receptor Agonists for the Treatment of Pain: Discovery of N,N-Diethyl-3-hydroxy-4-(spiro[chromene-2,4′-piperidine]-4-yl) Benzamide (ADL5747) - Le Bourdonnec, Bertrand; Windh, Rolf T.; Leister, Lara K.; Zhou, Q. Jean; Ajello, Christopher W.; Gu, Minghua; Chu, Guo-Hua; Tuthill, Paul A.; Barker, William M.; Koblish, Michael; Wiant, Daniel D.; Graczyk, Thomas M.; et al. (Journal of medicinal chemistry, 2009)
Selective, nonpeptidic δ opioid receptor agonists have been the subject of great interest as potential novel analgesic agents. The discoveries of BW373U86 (1) and SNC80 (2) contributed to the rapid expansion of research in this field. However, poor drug-like properties and low therapeutic indices have prevented clinical evaluation of these agents. Doses of 1 and 2 similar to those required for analgesic activity produce convulsions in rodents and nonhuman primates. Recently, we described a novel series of potent, selective, and orally bioavailable delta opioid receptor agonists. The lead derivative, ADL5859 (4), is currently in phase II proof-of-concept studies for the management of pain. Further structure activity relationship exploration has led to the discovery of ADL5747 (36), which is approximately 50-fold more potent than 4 in an animal model of inflammatory pain. On the basis of its favorable efficacy, safety, and pharmacokinetic profile, 36 was selected as a clinical candidate for the treatment of pain.